2018
DOI: 10.1007/s00296-018-3931-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the data on pregnancy and lactation provided by patient information leaflets of anti-rheumatic drugs in Argentina

Abstract: To analyse the level of consistency and updating of the information on pregnancy and lactation provided by patient information leaflets (PILs) of the antirheumatic drugs approved in Argentina. Inconsistencies between the 2016 EULAR Task Force recommendations on the use of anti-rheumatic drugs during pregnancy and lactation and the information provided by PILs of the same drugs approved in Argentina were analysed along with inconsistencies within the PILs of different registered trademarks of these drugs. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…With regard to information on antirheumatic drug therapy, recommendations from the EULAR and the British Society for Rheumatology have recently been published which represent a useful aid to assist clinicians in counseling patients 4 - 5 on leaflets of anti-rheumatic drugs showed that at least half of them had information inconsistencies which may compromise the consensual decision-making process between patient and health care professional 6 . This underlines the importance of dissemination and communication of clinical guidelines.…”
mentioning
confidence: 99%
“…With regard to information on antirheumatic drug therapy, recommendations from the EULAR and the British Society for Rheumatology have recently been published which represent a useful aid to assist clinicians in counseling patients 4 - 5 on leaflets of anti-rheumatic drugs showed that at least half of them had information inconsistencies which may compromise the consensual decision-making process between patient and health care professional 6 . This underlines the importance of dissemination and communication of clinical guidelines.…”
mentioning
confidence: 99%